The interactional ecology of homestay experiences: Locating input within participation and membership. (January 2023) - Greer, Tim; Wagner, Johannes
Study abroad homestays are generally assumed to provide visitors with opportunities to learn language 'in the wild' by participating in the host family's everyday life. Ultimately such participation is accomplished via individual episodes of interaction as the visitor is socialized into the family's mundane routines and rituals. Building on research into second language interaction in the lifeworlds of learners beyond the classroom, this study considers (1) how interactants in one homestay context draw on a range of ecologically available resources to co-accomplish participation and membership, and (2) how such participation affords the guest with an expanding repertoire of resources, including linguistic elements and new participatory practices. The study uses multimodal conversation analysis (CA) to discuss two extended extracts from naturally occurring interaction collected between a novice L2 English speaker and his homestay family. The analysis suggests that language learning is more complex than the mere provision of linguistic input: new lexical items and practices emerge within the interactants' respective lifeworlds in relation to locally situated contingencies, and can be occasioned and explained via recourse to a range of material and embodied affordances beyond just language. Input, therefore, is sequentially and ecologically located in the broader business of an ongoing collective sociality and primarily serves the two key interactional imperatives of progressivity and intersubjectivity.